solve for the unknown value in the give equation (1). 3 (12 - b) =...

solve for the unknown value in the give equation
(1). 3 (12 - b) = 2 (b - 6)
(2). 13p - 26 - p - 6 = 0?

To get notifications when anyone posts a new answer to this question,
Follow New Answers

Post an Answer

Please don't post or ask to join a "Group" or "Whatsapp Group" as a comment. It will be deleted. To join or start a group, please click here

Post UTME Past Questions 2019/2020
Latest WAEC Past Questions 2019 App - Free Download - 6643

Answers (3)

isaaq
1 month ago
See below.
EmX
1 month ago
For the first one.. remember to open the bracket first before attempting any solving.

See below.
1. 36-3b=2b-12
36+12=2b+3b
48=5b, b=48/5=9.6

2. 13p-p-26-6=0
12p=26+6
12p=32, p=32/12=2.67
Ask Your Own Question

Quick Questions

See More School-Based Questions Questions
 
Post UTME Past Questions 2019/2020
Post UTME Past Questions - 2019-2020 Exam Format + Free SMS Alerts - 6836
Latest WAEC Past Questions 2019 App - Free Download - 6643